Brain and behavioural organisation : EEG theta rhythm, neural unit activity and performance studied during normal behaviour and under acute alcohol influence - Laukka, Seppo, 1956- (Oulu : Oulun yliopisto, 1997)
Tiivistelmä. - Abstract.
Väitöskirja
Keywords: Alcohol Drinking; Behavior; Brain; Electroencephalography; Psychomotor Performance; Theta Rhythm; aivot; hjärna; psykomotoriikka; psykomotorik; Academic Dissertation; doktorsavhandlingar; väitöskirjat